Kinetically Stabilizing Mutations in Beta Tubulins Create Isotype-Specific Brain Malformations - Park, Kristen; Hoff, Katelyn J.; Wethekam, Linnea; Stence, Nicholas; Saenz, Margarita; Moore, Jeffrey K. (Frontiers in Cell and Developmental Biology, 2021)
Mutations in the family of genes encoding the tubulin subunits of microtubules are associated with a spectrum of human brain malformations known as tubulinopathies. How these mutations impact tubulin activity to give rise to distinct developmental consequences is poorly understood. Here we report two patients exhibiting brain malformations characteristic of tubulinopathies and heterozygous T178M missense mutations in different β-tubulin genes, TUBB2A or TUBB3. RNAseq analysis indicates that both TUBB2A and TUBB3 are expressed in the brain during development, but only TUBB2A maintains high expression in neurons into adulthood. The T178 residue is highly conserved in β-tubulins and located in the exchangeable GTP-binding pocket of β-tubulin. To determine the impact of T178M on β-tubulin function we created an analogous mutation in the β -tubulin of budding yeast and show that the substitution acts dominantly to produce kinetically stabilized microtubules that assemble and disassemble slowly, with fewer transitions between these states. In vitro experiments with purified mutant tubulin demonstrate that T178M decreases the intrinsic assembly activity of β-tubulin and forms microtubules that rarely transition to disassembly. We provide evidence that the T178M substitution disrupts GTPase-dependent conformational changes in tubulin, providing a mechanistic explanation for kinetic stabilization. Our findings demonstrate the importance of tubulin’s GTPase activity during brain development, and indicate that tubulin isotypes play different, important roles during brain development.